VAMP2 Expression and Genotype Are Possible Discriminators in Different Forms of Dementia - Costa, Andrea Saul; Ferri, Evelyn; Guerini, Franca Rosa; Rossi, Paolo Dionigi; Arosio, Beatrice; Clerici, Mario (Frontiers in Aging Neuroscience, 2022)
Vascular alterations often overlap with neurodegeneration, resulting in mixed forms of dementia (MD) that are hard to differentiate from Alzheimer’s Disease (AD). The 26bp intergenic polymorphism of VAMP2, a key component of SNARE complex, as well as its mRNA and protein levels are associated with neurological diseases. We evaluated ApoE4 and VAMP2 26bp Ins/Del genotype distribution in 177 AD, 132 MD, 115 Mild Cognitive Impairment (MCI) and 250 individuals without cognitive decline (CT), as well as VAMP2 gene expression in a subset of 73 AD, 122 MD, 140 CT and 103 MCI. Forty-two MCI evolved to AD (22 MCI-AD) or MD (20 MCI-MD) over time. VAMP2 mRNA was higher in MD compared to AD (p=0.0013) and CT (p=0.0017), and in MCI-MD compared to MCI-AD (p<0.001) after correcting for age, gender, MMSE and ApoE4+/- covariates (pc=0.004). A higher VAMP2 expression was observed in subjects carrying the minor allele Del compared to those carrying the Ins/Ins genotype (p=0.012). Finally, Del/Del genotype was more frequently carried by MD/MCI-MD compared to CT (pc=0.036). These results suggest that VAMP2 mRNA expression can discriminate mixed form of dementia from AD, possibly being a biomarker of AD evolution in MCI patients.